Angiotensin II type II receptors and colonic dysmotility in 2, 4‐dinitrofluorobenzenesulfonic acid‐induced colitis in rats. Issue 6 (3rd February 2017) - Zizzo, M. G.; Auteri, M.; Amato, A.; Caldara, G.; Nuzzo, D.; Di Carlo, M.; Serio, R.
Abstract: Background: Angiotensin II (Ang II), the main peptide of the renin‐angiotensin system (RAS), has been suggested to be involved in inflammatory bowel diseases. Since RAS has emerged as gut motility regulator, and dysmotility is associated with intestinal inflammation, our objective was to investigate in rat 2, 4‐dinitrobenzenesulfonic acid (DNBS)‐induced colitis the functionality of RAS and its contribution to colonic motor alterations. Methods: The effects of Ang II on the longitudinal colonic muscular contractility of control and DNBS‐treated rats were characterized in vitro . Transcripts encoding for Ang II receptors were investigated by RT‐PCR. Key Results: Inflamed preparations showed a longitudinal muscle marked hypocontractility. Angiotensin II caused contractile effects in both preparations, but the responses in DNBS preparations were reduced compared to controls. In both preparations, Losartan, AT1 receptor antagonist, reduced Ang II effects. PD123319, AT2 receptor antagonist, enhanced Ang II responses only in DNBS rats, as well as N ω ‐Nitro‐L‐arginine (L‐NNA), nitric oxide (NO) synthase inhibitor, or tetrodotoxin (TTX), neural toxin. The co‐administration of PD123319 and TTX or L‐NNA produced no additive effects. PD123319 per se improved colonic contractility in inflamed tissues. The effect was reduced in the presence of L‐NNA or TTX. All Ang II receptor subtypes were expressed in both preparations. Conclusions & Inferences: AT1 receptors mediate Ang II contractile responses in rat colon. During inflammation a recruitment of Ang II AT2 receptors would counteract AT1 ‐contractile activity. A tonic activation of AT2 receptors would contribute to the general reduction in muscle contractility during experimental inflammation. A role for enteric neurons and NO is also suggested. Abstract : Our objective was to investigate in rat 2, 4‐dinitrobenzenesulfonic acid (DNBS)‐induced colitis the functionality of RAS and its contribution to colonic dysmotility. Results indicate that AT1 receptors mediate Angiotensin II contractile responses in rat colon. During inflammation a recruitment of Angiotensin II AT2 receptors would counteract AT1 ‐contractile activity. A tonic activation of AT2 receptors would contribute to the general reduction in muscle contractility during experimental inflammation. A role for enteric neurons and NO is also suggested.